2022
DOI: 10.1108/imefm-02-2020-0062
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of Shariah-Compliant products to SDGs attending through the pace of economic growth: an empirical evidence from Pakistan

Abstract: Purpose Since 2004, Pakistan carried the banking sector under the umbrella of the Islamic financial paradigm, consequently the Islamic Banking Industry (IBI) placed an upright position in the banking and financial market of Pakistan. In this context, this study aims to analyze the effect of Shariah-compliant products of the IBI on the pace of economic growth in Pakistan. Design/methodology/approach The data set covered 13 Pakistani Islamic banks comprising four full-fledged Islamic banks and 9 conventional b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Gani & Bahari, 2020 [23] revealed in their research that Islamic Bank Financing has a long-term effect but, not in the short term on real GDP in Malaysia. There is also according to Siddique et al, 2022 [13] the financing variable has an influence on real GDP in Pakistan to encourage the achievement of SDGs and according to Ghoniyah & Hartono, 2020 [12] states that the Islamic banking financing variable in Indonesia makes a positive contribution to SDGs. Meanwhile, Frita et al, 2022 [24] states that financing has no influence on GRDP in the SDGs program.…”
Section: Resultsmentioning
confidence: 99%
“…Gani & Bahari, 2020 [23] revealed in their research that Islamic Bank Financing has a long-term effect but, not in the short term on real GDP in Malaysia. There is also according to Siddique et al, 2022 [13] the financing variable has an influence on real GDP in Pakistan to encourage the achievement of SDGs and according to Ghoniyah & Hartono, 2020 [12] states that the Islamic banking financing variable in Indonesia makes a positive contribution to SDGs. Meanwhile, Frita et al, 2022 [24] states that financing has no influence on GRDP in the SDGs program.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the results of this study, three interesting things were found related to Islamic sustainable finance, including development, social, and waqf. The word 'development' relates to Islamic Sustainable Finance, where one of the objectives of the ISF is for a country's economic growth (Ahmed, 2021;Alhammadi, 2022;Khan & Badjie, 2022;Ul-Hassan & Usman, 2013;Rarasati & Sambill, 2019;Saleem et al, 2021;Siddique et al, 2022). This is in line with the contribution of Islamic finance to global finance which has increased where based on global economic report data which estimates Islamic financial assets to reach $2.52 trillion, an increase of 13.9% from the previous year and Indonesia won the achievement as IFCI's first rank in the Global Islamic Finance Report 2021 (Nur, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…4. Economic Growth and Infrastructure Development (SDG 8 & 9): IBF promotes financial inclusion, which fosters economic growth and job creation (Siddique et al, 2022). Sharia-compliant financing instruments support infrastructure development projects, contributing to sustainable and inclusive economic growth (Zeb et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%